2011
DOI: 10.1111/j.1468-3083.2011.04304.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of glycerol and paraffin in the treatment of ichthyosis in children: an international, multicentric, randomized, controlled, double‐blind study

Abstract: Dexeryl showed a significant improvement of xerosis and related symptoms in children with ichthyosis and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
17
0
3
Order By: Relevance
“…In addition, there was a high risk of selection bias due to incomplete allocation concealment in one study [22] and a high risk of performance bias due to incomplete blinding of participants in one study [15]. Two studies had high drop-out rates that resulted in a high risk of attrition bias [33,35]. Taken together, a high risk of bias via at least one mechanism was encountered in five of the eight studies.…”
Section: Glycerinmentioning
confidence: 89%
See 3 more Smart Citations
“…In addition, there was a high risk of selection bias due to incomplete allocation concealment in one study [22] and a high risk of performance bias due to incomplete blinding of participants in one study [15]. Two studies had high drop-out rates that resulted in a high risk of attrition bias [33,35]. Taken together, a high risk of bias via at least one mechanism was encountered in five of the eight studies.…”
Section: Glycerinmentioning
confidence: 89%
“…All were double-blind randomized controlled trials with approximately 4 weeks of follow-up. The largest of these studies included 231 children with ichthyosis and showed that glycerin reduced pruritus (p = 0.01) and increased the number of responders (60.3 vs. 43.5 %, p = 0.008) compared with vehicle alone [33]. In a study in 151 adult patients with AD, glycerin significantly reduced dryness and irritation as evaluated by a dermatologist (p = 0.0004) [29].…”
Section: Glycerinmentioning
confidence: 95%
See 2 more Smart Citations
“…However, itch has occasionally been reported as an additional parameter in several studies, for instance when investigating the effect of topical therapies in ichthyosis. In a study where an emollient cream was used to reduce the severity of ichthyosis, the cutaneous xerosis evolution was assessed as a primary criterion using the SRRC score and pruritus was assessed as a secondary criterion . On a visual analogue scale [VAS ranging from 0 (no itch) to 10 (very severe)], pruritus at baseline was scored 3.41 and 3.76 in the vehicle and treatment group, respectively.…”
Section: Discussionmentioning
confidence: 99%